SEJARAH SOSIAL DAN KEHIDUPAN EKONOMI SUKU ANAK DALAM MUSLIM KECAMATAN AIR HITAM KAWASAN TAMAN NASIONAL BUKIT DUABELAS - Attohiroh, Attohiroh; Doni Nofra (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2024)
This research aims to explain how social and economic life of the Suku Anak Dalam that have been joined to Muslim. The Suku Anak Dalam is one of the remote tribes in Jambi Province. Previously, this tribe lived a simple life where they only ignored their lives in nature. However, over time, many changes have occurred in this tribe, many factors have caused these changes, one of which is interaction with outside society. This research is a type of field study research with a qualitative approach. Researchers went directly to the research location and conducted interviews with key sources, namely the Suku Anak Dalam, who are Muslims. The data analysis carried out in this research went through a series of steps in historical research methods which were preceded by heuristics, source criticism, interpretation and also historiography. The results of this research show that in 1998 the Suku Anak Dalam had already joined to Islam, they had abandoned old traditions such as melangun and basale, they had followed the way of life and rules of the village community, in addition, in terms of economics, they not only met their needs. just to eat, but already thinking about owning property.